Hypertonic saline and reduced peroxynitrite formation in experimental pancreatitis - Rios, Ester Correia Sarmento (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2011)
OBJECTIVES: In this study, we tested the hypothesis that hypertonic saline exerts anti-inflammatory effects by modulating hepatic oxidative stress in pancreatitis. INTRODUCTION: The incidence of hepatic injury is related to severe pancreatitis, and hypertonic saline reduces pancreatic injury and mortality in pancreatitis. METHODS: Wistar rats were divided into four groups: control (not subjected to treatment), untreated pancreatitis (NT, pancreatitis induced by a retrograde transduodenal infusion of 2.5% sodium taurocholate into the pancreatic duct with no further treatment administered), pancreatitis with normal saline (NS, pancreatitis induced as described above and followed by resuscitation with 0.9% NaCl), and pancreatitis with hypertonic saline (HS, pancreatitis induced as described above and followed by resuscitation with 7.5% NaCl). At 4, 12, and 24 h after pancreatitis induction, liver levels of inducible nitric oxide synthase (iNOS), heat-shock protein 70, nitrotyrosine (formation of peroxynitrite), nitrite/nitrate production, lipid peroxidation, and alanine aminotransferase (ALT) release were determined. RESULTS: Twelve hours after pancreatitis induction, animals in the HS group presented significantly lower iNOS expression (P<0.01 vs. NS), nitrite/nitrate levels (P<0.01 vs. NS), lipid peroxidation (P<0.05 vs. NT), and ALT release (P<0.01 vs. NS). Twenty-four hours after pancreatitis induction, nitrotyrosine expression was significantly lower in the HS group than in the NS group (P<0.05). DISCUSSION: The protective effect of hypertonic saline was related to the establishment of a superoxide-NO balance that was unfavorable to nitrotyrosine formation. CONCLUSIONS: Hypertonic saline decreases hepatic oxidative stress and thereby minimizes liver damage in pancreatitis.